A construção de um movimento negro em Marechal Cândido Rondon-PR: um estudo sobre as manifestações pós-emergência da lei 10.639/03. - Silva, José Ediane Pereira da (2016)
Grounded in actions and demonstrations in Marechal Cândido Rondon (PR), the dissertation is the central focus in the post-Emergency Law 10.639/03, which deals with the subject of great interest of the black population. Analyses were made with the intention of realizing the actions express the construction of social movement black spot. Investigations have as timeframe, the first initiatives undertaken in mid-2008, extending to 2014. To facilitate understanding of the subject, the studies report to the coming general context of black Africans to work in slave system in Brazil. Cover also the resistance against the system. And also include the emergence of the black social movement during the Brazilian republican period. Based on this context and in the reflections of the theory of social movements the study sought to understand references that supported the law 10.639/03. From the knowledge of the content of the law in 2008, a group of people from Rondon began producing actions aimed at enhancement of the black people in history and today in Brazil, including in the city. With the analysis of the stock, it was revealed the interdisciplinary content of the law in question. Similarly, it was also the basis for the work, analysis of bibliographies that depict the historical context of the city as well as documents, if the Statute of OERAN - Ethnic Organization Racial Nagô of Marechal Cândido Rondon, debated and voted on application in camera councilors, Statute of Racial Equality, Themed Notebooks of Paraná State Education: History and african-Brazilian culture and African / Law 10.639/03. For the same purpose, photographic records and information published in newspapers about actions and events in the locality and also on sites were observed, such as the Secretariat of the State of Paraná Education, and black organizations and social movements. With this support, actions and practices were analyzed aimed to build black social movement in Marechal Cândido Rondon